2018
DOI: 10.1186/s13054-017-1933-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolic effects of strict versus conventional glycaemic targets following severe traumatic brain injury

Abstract: BackgroundOptimal glycaemic targets for patients with severe traumatic brain injury remain unclear. The primary objective of this microdialysis study was to compare cerebral metabolism with strict versus conventional glycaemic control.MethodsWe performed a prospective single-centre randomised controlled within-subject crossover study of 20 adult patients admitted to an academic neurointensive care unit with severe traumatic brain injury. Patients underwent randomised, consecutive 24-h periods of strict (4–7 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(75 citation statements)
references
References 28 publications
3
72
0
Order By: Relevance
“…However, intensive insulin therapy was associated with markers of neurotoxicity and metabolic distress, such as higher glutamate (p < 0.01) and LPR (p < 0.03) and lower brain glucose (p < 0.05) (Vespa et al, 2006). Similar findings from observational and comparative studies later confirmed the increased risk of brain metabolic distress and reduced brain glucose related to aggressive insulin treatment and tight glycemic control (Vespa et al, 2006;Oddo et al, 2008;Schlenk et al, 2008;Meierhans et al, 2010;Plummer et al, 2018).…”
Section: Systemic and Brain Glucosementioning
confidence: 61%
“…However, intensive insulin therapy was associated with markers of neurotoxicity and metabolic distress, such as higher glutamate (p < 0.01) and LPR (p < 0.03) and lower brain glucose (p < 0.05) (Vespa et al, 2006). Similar findings from observational and comparative studies later confirmed the increased risk of brain metabolic distress and reduced brain glucose related to aggressive insulin treatment and tight glycemic control (Vespa et al, 2006;Oddo et al, 2008;Schlenk et al, 2008;Meierhans et al, 2010;Plummer et al, 2018).…”
Section: Systemic and Brain Glucosementioning
confidence: 61%
“…A network meta‐analysis was performed using 35 RCTs. 366 , 620 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 , 700 , 701 , 702 , 703 , 704 , 705 , 706 , 707 , 708 , 709 We divided target blood glucose levels into less than 110 mg/dL, 110–144 mg/dL, 144–180 mg/dL, and > 180 mg/dL. The results showed that the estimated values of mortality were as follows: when compared to < 110 mg/dL, a range of 110–144 mg/dL yielded a RD of 40 fewer per 1,000 (95%CI: 100 fewer to 30 more) (1 RCT, n = 90), a range of 144–180 mg/dL yielded an RD of 27 fewer per 1,000 (95%CI: 45 fewer to 8 fewer) (5 RCTs, n = 7,323), and a range > 180 mg/dL yielded an RD of 4 more per 1,000 (95%CI: 22 fewer to 35 more) (12 RCTs, n = 8,027).…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
“…Human insulin (Wan-Bang Biochemical Medicine Ltd., XuZhou, JiangSu, China) was instilled intravenously at 1IU/ml at the speed of 2-20 IU/h within 2-4 h via microinfusing pump (MP-30, Medcaptain, Shenzhen, China). The target conventional glycemic level is maintained at 8.0-10.0 mmol/L [33,62]. During insulin infusion, glucose levels were measured repeatedly on xed time points between 1 and 2 h after the last glucose measurement [61].…”
Section: Intensive Insulin Therapymentioning
confidence: 99%
“…The substrate of NO synthase, L-arginine, its transport was diminished in platelets from obese and metabolic syndrome patients, and correlated negatively with insulin resistance [32] . TBI, as a severe stress, could provoke critical hyperglycemia [33,34] and central insulin resistance in human [35] and in mice [36], possibly due to central glutamate excitotoxicity [37] and endoplasmic reticulum stress to elevate sympathetic nerve tone [38], or through adipose-derived monocyte chemoattractant protein-1 (MCP-1) to increase coagulation factors [39]. Hence, peripheral insulin resistance following TBI in either human [40] or in mice [41,42] was an independent predictor of the mortality [40].…”
mentioning
confidence: 99%